Terapia laser de baixa intensidade a 808 nm reduz a resposta inflamatória e favorece a regeneração muscular - Assis, Lívia Ribeiro de (Universidade Federal de São Carlos, 2012)
Muscle regeneration is a complex phenomenon, involving coordinated activation of several cellular responses. During this process, oxidative stress, and consequent tissue damage occur with a severity that may depend on the intensity and duration of the inflammatory response. Among the therapeutic approaches to attenuate inflammation and increase tissue repair, low-level laser therapy (LLLT) may be a safe and effective clinical procedure. The aim of this study was to evaluate the effects of LLLT on oxidative/nitrative stress and inflammatory mediators produced during a cryolesion of the tibialis anterior (TA) muscle in rats. Sixty Wistar rats were randomly divided into three groups (n=20): control (BC), injured TA muscle without LLLT (IC), injured TA muscle submitted to LLLT (IRI). The injured region was irradiated daily for 4 consecutive days, starting immediately after the lesion using an AlGaAs laser (continuous wave, 808nm, tip area of 0.00785 cm2, power 30 mW, application time 47 s, fluence 180 J/cm2; total energy 1.4J; irradiance 3.8 mW/cm2). The animals were sacrificed on the fourth day after injury. LLLT reduced oxidative and nitrative stress in injured muscle, decreased lipid peroxidation, nitrotyrosine formation and NO production, probably due to reduction in iNOS protein expression. Moreover, LLLT increased SOD gene expression, and decreased the inflammatory response as measured by gene expression of NF-kβ and COX-2 and by TNF-α and IL-1β concentration. These results suggest that LLLT could be an effective therapeutic approach to modulate oxidative and nitrative stress and to reduce inflammation in injured muscle and could therefore help muscle regeneration.
Keywords: Fisioterapia; Regeneração muscular; Laser de baixa intensidade; Lesão muscular; Músculo estriado esquelético; Reabilitação; Low-level laser therapy; Photobiomodulation; Muscle cryolesion; Inflammatory mediators; Nitrative stress; Oxidative stress; Muscle regeneration; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL